Complete mitochondrial genome of Gymnodiptychus pachycheilus (Teleostei: Cypriniformes: Cyprinidae). (2nd January 2016) - Wu, Bo; Deng, Yuanping; Wu, Jiayun; Yan, Chaochao; Song, Zhaobin
Abstract: The complete mitochondrial DNA genome of Gymnodiptychus pachycheilus was sequenced and characterized. The genome is 16, 586 bp in length. As with most teleosts, the mitogenome of G. pachycheilus is structurally conserved, containing two ribosomal RNA (rRNA) genes, 13 protein-coding genes, 22 transfer RNA (tRNA) genes and one displacement loop (D-loop) region. The 12 heavy-strand protein-coding genes of G. pachycheilus and other 15 Schizothoracinae species were used for phylogenetic analysis by Bayesian inference and maximum likelihood methods. The topology demonstrated that G. pachycheilus is relatively close to species in genera of Gymnocypris, Schizopygopsis and Oxygymnocypris but differentiated earlier in Schizothoracinae than them.